Monte Carlo simulation of shielded chair whole body counting system with Masonite cut sheet phantom. (May 2015) - Manohari, M.; Mathiyarasu, R.; Rajagopal, V.; Venkatraman, B.
Abstract: The shielded chair wholebody counting system used at IGCAR is calibrated experimentally using Masonite cut sheet phantom loaded with single radionuclide of known activity. Multiple point sources of a particular radionuclide are distributed at mid-thickness in each segment of the phantom during calibration. Though the detector can be used for the measurement of gamma photons upto 3000 keV, the experimental calibration is done only upto 1500 keV according to the requirement of measurement of fission and activation products, which emits gamma energies predominantly in the regions below 1500 keV. The expertize in numerical Monte Carlo simulation was utilized to obtain the efficiency values above 1500 keV. This paper focuses on the validation of the shielded chair counting system model using the Masonite cut sheet phantom measurements and applying the validated model to extend the energy range of the calibration upto 3 MeV. A good agreement of the theoretically simulated and experimental 137 Cs spectrum with respect to the spectral shape, counts in all the energy regions and the photopeak efficiency validated the modeling of the counting system. A mathematical function to fit the counting efficiencies with photon energies was developed and a set of fitting parameters were established so that the efficiency value of any energy upto 3 MeV can be obtained without performing experimental efficiency calibration. The efficiency values obtained from the fit were compared with experimental ones and found to be in agreement, i.e., within 8% for the 250–1500 keV energy range. The Compton scattering factors (CSFs) at different low energies due to high energy photons were also simulated. The theoretical and experimental CSFs were compared and found to be matching within ±20%. Simulations with uniform source distribution inside the Masonite phantom has shown that the current source distribution followed at IGCAR gives efficiency values within ±5% compared to that of uniform distribution. Highlights: MCNP modeling of the shielded chair wholebody counting system with the Masonite phantom and its validation using experiments. Theoretical simulation of efficiency values and CSFs for different energies. Established an equation to estimate the efficiency values in the energy range 250–3000 keV. Theoretically established that the present multiple point source distribution at mid-thickness closely represents the uniform source distribution.